The expression of growth factor signaling genes in co-culture IVM - Erif Maha Nugraha Setiawan; Hyun Ju Oh; Min Jung Kim; Geon A Kim; Seok Hee Lee; Yoo Bin Choi; Ki Hae Ra; Byeong Chun Lee (Universitas Gadjah Mada, 2017)
The objective of this study was to determine the expression of growth factor signaling genes in human adiposederived stem cells (ASCs), porcine oocytes, and cumulus during in vitro maturation (IVM). The human ASCs (from 2 young and 2 old donors) were used for the co-culture IVM system. The maturation rate was examined based on polar body extrusion. The expression of the growth factor signaling genes from ASCs, oocytes, and cumulus were measured using qPCR. All data were analyzed using ANOVA followed by Tukey’s test. The expression of the h-IGF1 signaling genes from human ASCs cells showed similar values in all groups and the h-FGF2 expressions were higher in the young donors than the old ones. The p-FGF2, p-FGFR2, and p-TGFβ1 expressions in the oocytes as well as p-IGFR in the cumulus that were co-cultured from the young donors showed higher values than the old and control groups. The apoptotic ratio (p-BAX/p-BCL2) from the oocytes and cumulus in both co-culture groups also showed lower levels than the control (P<0.05). Oocyte maturation rates were significantly increased in all co-cultured groups (Y1 (85.9 ± 2.2%), Y2 (91.2 ± 1.1%), O1 (86.3 ± 1.5%), and O2 (86.5 ± 2.3%)) compared with the control (76.7 ± 1.1%; P<0.05). Although the expression of growth factor signaling genes was varied, young donors’ ASCs might support in vitro maturation beħer than those from old donors.